2015
DOI: 10.1016/j.energy.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Customer-driven design of the recharge infrastructure and Vehicle-to-Grid in urban areas: A large-scale application for electric vehicles deployment

Abstract: a b s t r a c tThe large scale deployment of electric vehicles in urban environment will play a key-role over the next decades to reduce air-pollutants in densely populated areas, but it will also require the development of an adequate recharge infrastructure. The purpose of this paper is to demonstrate how driving patterns databases and data mining can be used to appropriately design this infrastructure. This application focuses on the Italian province of Firenze, involving about 12,000 conventional fuel vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…On the other hand, EVs/PHEVs with vehicle to grid (V2G) connection capability have been introduced in the literature [26,27]. Analysis of different impacts of EVs/PHEVs with V2G connection capability on electric power distribution systems is an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, EVs/PHEVs with vehicle to grid (V2G) connection capability have been introduced in the literature [26,27]. Analysis of different impacts of EVs/PHEVs with V2G connection capability on electric power distribution systems is an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study on households using smart washing machines reported that demand automatically shifted to periods when electricity is not expensive [75]. Advanced storage and peak-shaving technologies can be used to reduce the peak load [76][77][78]. Electrochemical technology-based battery energy storage system (BESS) is mostly used for peak-shaving.…”
Section: Various Concepts Aligned With the Smart Gridmentioning
confidence: 99%
“…The models mentioned above tend to focus on the early phase of a charging infrastructure roll-out [5,7,8]. Traffic flow data and GPS data are used to model charging infrastructure locations [8,12], not taking into account real-life utilization of the charging infrastructure. Only a few studies use real-life charging data to either model or assess the utilization of the charging infrastructure.…”
Section: Charging Infrastructure Planning Design and Locationmentioning
confidence: 99%